Incidence, Mortality, and Outcome-Predictors of Sudden Cardiac Arrest Complicating Myocardial Infarction Prior to Hospital Admission. (January 2019) - Karam, Nicole; Bataille, Sophie; Marijon, Eloi; Tafflet, Muriel; Benamer, Hakim; Caussin, Christophe; Garot, Philippe; Juliard, Jean-Michel; Pires, Virginie; Boche, Thévy; Dupas, François; Le Bail, Gaelle; et al.
Abstract : Background: Mortality of ST-segment–elevation myocardial infarction (STEMI) decreased drastically, mainly through reduction in inhospital mortality. Prehospital sudden cardiac arrest (SCA) became one of the most feared complications. We assessed the incidence, outcome, and prognosis' predictors of prehospital SCA occurring after emergency medical services (EMS) arrival. Methods and Results: Data were taken between 2006 and 2014 from the e-MUST study (Evaluation en Médecine d'Urgence des Strategies Thérapeutiques des infarctus du myocarde) that enrolls all STEMI managed by EMS in the Greater Paris Area, including those dead before hospital admission. Among 13 253 STEMI patients analyzed, 749 (5.6%) presented EMS-witnessed prehospital SCA. Younger age, absence of cardiovascular risk factors, symptoms of heart failure, extensive STEMI, and short pain onset-to-call and call-to-EMS arrival delays were independently associated with increased SCA risk. Mortality rate at hospital discharge was 4.0% in the nonSCA group versus 37.7% in the SCA group ( P <0.001); 26.8% of deaths occurred before hospital admission. Factors associated with increased mortality after SCA were age, heart failure, and extensive STEMI, while male sex and cardiovascular risk factors were associated with decreased mortality. Among patients admitted alive, PCI was the most important mortality-reduction predictor (odds ratio, 0.40; 95% CI, 0.25–0.63; P <0.0001). Conclusions: More than 1 of 20 STEMI presents prehospital SCA after EMS arrival. SCA occurrence is associated with a 10-fold higher mortality at hospital discharge compared with STEMI without SCA. PCI is the strongest survival predictor, leading to a twice-lower mortality. This highlights the persistently dramatic impact of SCA on STEMI and the major importance of PCI in this setting.